2014
DOI: 10.2215/cjn.11601113
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Heart Failure and Worsening Kidney Function

Abstract: There is high prevalence of CKD, defined by reduced GFR, in patients with heart failure. Reduced kidney function is associated with increased morbidity and mortality in this patient population. The cardiorenal syndrome (CRS) involves a bidirectional relationship between the heart and kidneys whereby dysfunction in either may exacerbate the function of the other, but this syndrome has been difficult to precisely define because it has many complex physiologic, biochemical, and hormonal abnormalities. The pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 73 publications
0
18
0
1
Order By: Relevance
“…In addition, more patients with stage 3 CKD were also included in this study compared with our study. It is well known that certain clinical factors, such as diabetes, proteinuria, heart failure, and baseline eGFR, could exacerbate the eGFR decline rate in patients with CKD [28][29][30][31]. In our study, although pharmacologic urate-lowering therapy was not related to kidney survival, univariate Cox regression analysis revealed that the above-mentioned clinical factors were also the significant prognostic factors for kidney survival.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, more patients with stage 3 CKD were also included in this study compared with our study. It is well known that certain clinical factors, such as diabetes, proteinuria, heart failure, and baseline eGFR, could exacerbate the eGFR decline rate in patients with CKD [28][29][30][31]. In our study, although pharmacologic urate-lowering therapy was not related to kidney survival, univariate Cox regression analysis revealed that the above-mentioned clinical factors were also the significant prognostic factors for kidney survival.…”
Section: Discussionmentioning
confidence: 45%
“…Kidney and cardiac dysfunction frequently coexist, reflecting common factors in their aetiology including diabetes, hypertension, atherosclerosis and left ventricular hypertrophy [14]. The cardio-renal syndrome describes the bidirectional relationship between the heart and kidneys whereby dysfunction in either may cause deterioration in the function of the other [14][15][16].…”
Section: Recurrent Episodes Of Aki In Diabetic Kidney Disease Results mentioning
confidence: 99%
“…In addition, the same animal was associated with increased heart and kidney somatic index. Cardiorenal interaction in congestive heart failure has been increasingly recognized in medicine (SARNAK, 2014;DAMMAN & TESTANI, 2015).…”
Section: Discussionmentioning
confidence: 99%